Perian Semantik Leksem Verba Bermakna ‘Menyakiti’ dalam Bahasa Konjo Dialek Konjo Pesisir: Description of Semantical Lexeme of The ‘Hurt’ Meaning Verb in The Coastal Area Dialect of Konjo - Normawati, Normawati (Kibas Cenderawasih, 2023)
This essay has an effort to review any verbal domain which has meaning “hurt” in Konjo, especially in Konjo coastal area dialect as well as any meaning components of each verb. The method which is used is qualitative descriptive. Oral sources obtained from any daily speaking of Coastal Konjo’s dialect. The result shows that there are 52 lexemes of “hurt” meaning verb in this dialect. These lexemes are classified into four groups, namely, (1) hurt with hand, (2) hurt with leg, (3) hurt with teeth, and (4) hurt with tools. Verb which is meant “hurt with hand” is again, classified into 5 ways, they are , ‘hit’, ‘press’, ‘drag’, ‘push’, and ‘twist’. Verb which is meant ‘hurt with leg’ is classified into four lexemes, they are  lisa’ ‘step on’, semba’ ‘kick’, tuddu’ ‘kick’, dan piring ‘kick’. Verb which is meant ‘hurt with teeth’ is divided into two lexemes, namely, kikki’/kokko’ ‘bite’ dan karappu’ ‘bite’. Verb with meaning ‘hurt with tools’ is classified into four ways, they are, ‘beat’, ‘fling’, ‘cut’, and ‘stab’.